Anterior iris‐claw intraocular lens implantation for the management of nontraumatic ectopia lentis: long‐term outcomes in a paediatric cohort. Issue 2 (18th August 2016) - Català‐Mora, Jaume; Cuadras, Daniel; Díaz‐Cascajosa, Jesús; Castany‐Aregall, Marta; Prat‐Bartomeu, Joan; García‐Arumí, José
Abstract: Purpose: To report the feasibility and long‐term safety of lensectomy and iris‐claw intraocular lens (IOL) implantation to treat children with severe ectopia lentis in a paediatric tertiary hospital. Methods: Prospective cohort study of 21 eyes from 12 patients with severe ectopia lentis and visual acuity <20/63. All eyes underwent 23‐gauge pars plana vitrectomy, lensectomy, iridectomy and Artisan IOL implantation in the anterior chamber with iris‐claw enclavation via pars plana. Mean age at surgery was 8.0 ± 5.3 yo (range 3–17 years). A full ophthalmologic examination including best‐corrected visual acuity (BCVA), biomicroscopy, intraocular pressure (IOP) measurement, fundus evaluation and central endothelial cell count (cECC) was performed pretreatment, at 3 months' postsurgery, and every 6 months thereafter. Ultrasound biomicroscopy (UBM) was performed 12 months after surgery. Results: Mean follow‐up was 39.3 ± 13.0 months. Best‐corrected visual acuity (BCVA) (mean ± SD) improved from 0.91 ± 0.29 logMar preoperatively to 0.18 ± 0.23 logMar at final follow‐up (p < 0.0001). Mean distance from the endothelium to the anterior IOL surface after surgery was 3.11 ± 0.61 mm. Postsurgically, cECC loss was 5.04% ± 9.58% with an annual cECC loss rate of 3.16% ± 4.46%. One patient developed IOL dislocation and retinal detachment after severe ocular contusion requiring vitrectomy, IOL refixation and gas tamponade. Another patient developed cystoid macular oedema, managed with intravitreal dexamethasone. Conclusion: This technique is both feasible and effective to manage severe ectopia lentis in children. Lifetime ophthalmic follow‐up including cECC measurement, IOL position monitoring and fundus examination is mandatory in these patients.